Перемены в беспоповстве и федосеевский собор 1752 г. - Поташенко, Григорий (Slavistica Vilnensis, 2001)
The article examines the ecclesiastical and moral/religious circumstances of the Priestless Old Believers, and the changes in their confession that occurred in the mid-18th century. The focus of the analysis are the reasons for the convocation of the Fedoseev Cathedral in Gudishki (now the Ignalin region of Lithuania) in 1752, and its decrees. The so-called “Polish Cathedral” condemned the Novozheny movement, which had arisen among a part of the Priestless Old Believers. This was an extremely important event in the life of the Fedoseev community of the Grand Duchy of Lithuania and Poland, and it had considerable inflluence on the history of the Fedoseevism as a whole.